Advanced Characterization Techniques for Identifying the Key Active Sites of Gas‐Involved Electrocatalysts. (8th July 2020) - Da, Yumin; Li, Xiaopeng; Zhong, Cheng; Deng, Yida; Han, Xiaopeng; Hu, Wenbin
Abstract: Highly efficient electrocatalysts play an integral part in developing renewable energy conversion and storage technologies. Despite considerable efforts devoted to synthesizing electrocatalysts with superior performance, the identification of active moieties and understanding of reaction mechanisms under practical conditions still remain elusive. Herein, the substantial progresses in unraveling the local electronic and atomic structure optimizations of nanocatalysts for gas‐involved electrocatalysis, disclosing real active sites, and clarifying their relationships with intrinsic activities by combining advanced characterization techniques with computational simulations are summarized. The continuous development of in situ and ex situ characterization tools, particularly at multi‐scale resolution, to monitor or even directly observe the active center structure is systematically discussed, which is divided into four main categories based on the type of active sites: atomically dispersed active sites, vacancies, heteroatom doping sites, and edge sites. Current challenges and perspectives in both fundamental area and industrial application are finally proposed for the future research direction of next‐generation electrode materials. The aim of this review is to provide mechanistic insights into the real catalytically active structure with the assistance of newly developed characterization techniques, guiding the rational design and structure engineering of advanced functional materials with outstanding activity, selectivity, and durability. Abstract : Identifying catalytically active sites and clarifying structure–activity relationships are critical to synthesize efficient electrocatalysts for various energy conversion technologies. Herein, a comprehensive review of recent progresses on this attractive topic with the assistance of advanced characterization techniques is provided. Current challenges and future directions are discussed to guide the rational design of electrocatalysts with outstanding activity, selectively, and durability.